Extração e prospecção de metabólitos secundários de folhas de Annona glabra L. e análise de atividade sobre o crescimento de coleóptilos de trigo e de microorganismos - Matsumoto, Reginaldo Sadao (2013)
The record of Annonaceae substances increases every year, as well as the isolation of bioactive compounds in this family. Currently there is a growing demand in the discovery of natural substances less toxic than synthetic products that are herbicides, algaecides and bactericides. For this reason bio-prospection, identification and production of secondary metabolites has become increasingly important. Numerous studies on the chemical composition of Annona glabra L. were made using their seeds, fruits, stems and fewer leaves. However, the major activities studied are related to the inhibition of tumor cells. One of the major difficulties of conducting phytochemical studies is to obtain sufficient amounts of purified product for the biological testing and its economic exploitation through the subsequent synthesis of these substances. Besides the amount of substance isolated is also important to reduce costs related to such a process. The present study was designed from the preliminary results on the allelopathic effects of extracts of Annona glabra on seed germination and also due to the need for optimization of extraction of bioactive substances for use as algaecides and fungicides. Two procedures were assistants to extraction (ultrasound-assisted extraction (UAE) and microwave assisted extraction (MAE)) in bio-directed activity assays on wheat-etiolated coleoptiles. After the optimization process, an extraction mass (UAE) was performed to isolate and identify the major substances: (1) (-)-Kaur-16-en-19-oic acid, (2) β- sitosterol, (3) Stigmasterol, (4) ent-19-methoxy-19-oxokauran-17-oic acid, (5) 16α- hydro-19-acetoxy-ent-kauran-17-oic acid (annoglabasin B), (8) Asimicin and minor substances (6) ent-17-hydroxykaur-15-en-19-oic acid e (7) ent-15β,16β-epoxy-17- hydroxy-kauran-19-oic acid. Wherein the substance 5 was highly inhibitory against coleoptiles followed by the substances 4 and 8. The acetonic extract showed growth retardation of Selenastrum capricornutum in concentrations of 125-175 mgL-1 and fully inhibitory above 200 mgL-1 and IC50, at 96h, was 145 mgL-1. The oomycete Pythium aphanidermatum was inhibited at concentrations above 125 μg.disc-1. These results highlight the importance of bioprospecting of substances of this species and opening up opportunities for future commercial uses.